Small mammals - Ganeri, Anita, 1961-; Parsons, John (New York : F. Watts, 1993)
Discusses the characteristics, habits, and natural habitat of a variety of small diurnal and nocturnal mammals. Also suggests activities for observing them and the signs and clues they leave behind.
Includes index.
Appraisal-Science Books for Young People.
Booklist.
5.8
5-8
Keywords: Mammals -- Miscellanea -- Juvenile literature; Mammals -- Miscellanea; Mammals -- Miscellanea